The Effect of a Polyvalent Antivenom on the Serum Venom Antigen Levels of Naja sputatrix (Javan Spitting Cobra) Venom in Experimentally Envenomed Rabbits. Issue 4 (15th April 2015) - Yap, Michelle Khai Khun; Tan, Nget Hong; Sim, Si Mui; Fung, Shin Yee; Tan, Choo Hock
Abstract The treatment protocol of antivenom in snake envenomation remains largely empirical, partly due to the insufficient knowledge of the pharmacokinetics of snake venoms and the effects of antivenoms on the blood venom levels in victims. In this study, we investigated the effect of a polyvalent antivenom on the serum venom antigen levels of Naja sputatrix (Javan spitting cobra) venom in experimentally envenomed rabbits. Intravenous infusion of 4 ml of Neuro Polyvalent Snake Antivenom [NPAV, F(ab′)2] at 1 hr after envenomation caused a sharp decline of the serum venom antigen levels, followed by transient resurgence an hour later. The venom antigen resurgence was unlikely to be due to the mismatch of pharmacokinetics between the F(ab′)2 and venom antigens, as the terminal half‐life and volume of distribution of the F(ab′)2 in serum were comparable to that of venom antigens (p > 0.05). Infusion of an additional 2 ml of NPAV was able to prevent resurgence of the serum venom antigen level, resulting in a substantial decrease (67.1%) of the total amount of circulating venom antigens over time course of envenomation. Our results showed that the neutralization potency of NPAV determined by neutralization assay in mice may not be an adequate indicator of its capability to modulate venom kinetics in relation to its in vivo efficacy to neutralize venom toxicity. The findings also support the recommendation of giving high initial dose of NPAV in cobra envenomation, with repeated doses as clinically indicated in the presence of rebound antigenemia and symptom recurrence.